'Complex' Crime Fiction and the Politics of Ongoing-ness: Don Winslow's War against Endings. (March 2020) - Pepper, Andrew
Abstract : In pointing out that beginnings and endings merge in Don Winslow's 'drug war' trilogy –  The Power of the Dog (2005), The Cartel (2015), and The Border (2019) – I argue that his narratives, like the 'war on drugs' itself, are 'ongoing.' Taking the resulting tension whereby this open-endedness or ongoing-ness is set against crime fiction's more typical generic push to resolution, as a starting point, I use and develop Mittell's concept of 'complex TV' to account for the complexities and continuities of Winslow's fiction. In one sense, this ongoing-ness is occasioned by Winslow's subject matter: it is the sociopolitical realities of the 'war on drugs' which determine the trilogy's structural and generic qualities. But what makes Winslow such an important writer are the particular ways he reshapes and pushes against the limits of narrative and genre, something that is made possible by and in turn makes possible a particular understanding of political struggle as ongoing and irresolvable. In my essay I explore the political implications of Winslow's fiction through a close examination of narrative and genre and where the emphasis is placed on breakdown and glitch rather than the successful realisation of totality.